SOCIOLINGUISTIC STUDY OF THE USE OF LANGUAGE IN THE TRADITIONAL RITUAL OF "PURUNG TA LIANG MARAPU" IN THE COMMUNITY OF CENTRAL SUMBA REGENCY - Diana Sabawaly; Paulus Mikku Ate (JURNAL KONFIKS, 2026)
The Purung Ta Liang Marapu ritual represents a sacred cultural practice of the Central Sumba community, employing a specialized form of language as a medium of transcendental communication with ancestral entities (Marapu). However, the meanings and functions of this ritual language remain largely inaccessible to the general community and are primarily confined to traditional authorities (Ratu). This study aims to analyze the use of language in the ritual and to identify its social, cultural, and religious-magical functions from a sociolinguistic perspective. This research employs a qualitative approach with a descriptive sociolinguistic method. Data were collected through participant observation, in-depth interviews with Ratu and traditional elders, and audio-visual documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that ritual language constitutes a sacred register characterized by archaic diction, parallelism, and formulaic expressions. Sociolinguistically, it functions as a mechanism of social legitimacy, a tool for social cohesion, and a medium for transmitting cultural values and Marapu beliefs. Additionally, ritual language exhibits performative properties that contribute to maintaining the balance between humans, ancestors, and the natural world. The limited public understanding is attributed to the exclusivity of oral transmission. Therefore, systematic linguistic documentation is essential to preserve cultural continuity and to bridge intergenerational knowledge gaps in the context of modernization.